a+7b+6c=-7

Simple and best practice solution for a+7b+6c=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for a+7b+6c=-7 equation:


Simplifying
a + 7b + 6c = -7

Solving
a + 7b + 6c = -7

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-7b' to each side of the equation.
a + 7b + -7b + 6c = -7 + -7b

Combine like terms: 7b + -7b = 0
a + 0 + 6c = -7 + -7b
a + 6c = -7 + -7b

Add '-6c' to each side of the equation.
a + 6c + -6c = -7 + -7b + -6c

Combine like terms: 6c + -6c = 0
a + 0 = -7 + -7b + -6c
a = -7 + -7b + -6c

Simplifying
a = -7 + -7b + -6c

See similar equations:

| 5+4(7+9)= | | 9x+8=8x+64 | | 7a-2b-9c=6 | | y=x^3-9x^2+15+5 | | 2a-3b-5c=4 | | 5(-3x+8)=-125 | | -3(-7+5x)=51 | | 6(6-2x)=156 | | 7(4x+4)=84 | | 2u+v+2w=-2 | | 7t^2+28t+8=0 | | 3(4x-3)=5(2x+1) | | 7(2x-2)=-112 | | 3m-9=6 | | 3x^4-6x^3-x+2=0 | | (x+3)(x+18)=180 | | 6(3o-0)=-36 | | -6x+10=6x+58 | | ln(x^2)+3lnx-2ln(3x)=lny | | 0-5(d-1.5)=2.5 | | 3-(3x+5)=0 | | 5+3x=6x+14 | | 6x-9=10x+5 | | -8v+1=7v-20 | | (3x+5)-3=0 | | 5+3x=6x+-14 | | 2(15-y)+6y=42 | | 50-2x=40+4x | | 2(6+7x)=166 | | 57=5x+12 | | 5u-3v+4w=-3 | | 16x^2-25x+9216=0 |

Equations solver categories